Hyper-plurality and the need for regulation of candidate entry in India - Bhattacharya, Kaushik; Mitra, Subrata K. (2013)
It is argued that given the high variation and lack of stability in candidate structure across regions and over time, a local approach on "signature requirement" - as in the United States - could be an effective deterrent to hyper-plurality in candidate entry in elections in India. Accordingly it is suggested that the Election Commission of India should not only have the power to determine the "electoral deposit" before each election, it should also have the power to change the minimum signature requirement across constituencies under certain pre-specified conditions. - Reproduced.
Keywords: Elections